2008
DOI: 10.1007/s10926-008-9128-1
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Return-to-work Interventions for Musculoskeletal Conditions Address the Multicausality of Work Disability?

Abstract: Interventions which involve the work environment and concerted action by the various partners seem to require the most investment in terms of energy. The establishment of common principles and shared values regarding work rehabilitation as well as less divided mechanisms for action among the various partners should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 28 publications
0
34
0
3
Order By: Relevance
“…These have ranged from minimal postal intervention, OH phone intervention to multidisciplinary approaches involving workplace assessment, work modifications and importantly case management involving all stakeholders (22)(23)(24)(25). However, to our knowledge there are far fewer studies or reviews of very early intervention under two weeks (26,27), despite the fact that there are a number of commercially successful companies offering sickness absence management services to employers, which involve the employee being telephoned on day one (28,29).…”
Section: Brown Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These have ranged from minimal postal intervention, OH phone intervention to multidisciplinary approaches involving workplace assessment, work modifications and importantly case management involving all stakeholders (22)(23)(24)(25). However, to our knowledge there are far fewer studies or reviews of very early intervention under two weeks (26,27), despite the fact that there are a number of commercially successful companies offering sickness absence management services to employers, which involve the employee being telephoned on day one (28,29).…”
Section: Brown Et Almentioning
confidence: 99%
“…Demou et al (34) have described the rationale and implementation of the EASY service in NHSL. In brief, this new telephonebased sickness absence management service provides early intervention based on the biopsychosocial model (35) applying cognitive behavioral principles, and utilizing evidence-based interventions (16,(22)(23)(24)36). A brief description of the process follows.…”
Section: Brown Et Almentioning
confidence: 99%
“…A review of workplace interventions has shown that the interventions are more focused on changing and improving the individual's prerequisites for return to work than making changes in work environment and organisation [35]. The most common workplace interventions are directed towards stress management, retraining in work tasks, and accommodations made at the workplace to help the worker adjust to the work task requirements [36]. In addition, a comparative study, investigating if cross country differences could explain differences in return to work after occupational back pain, showed that Sweden was one of the countries that did not use workplace interventions to any extent for promoting the return-to-work process [37].…”
Section: The Roles and Responsibilities Of Supervisors And Co-workersmentioning
confidence: 99%
“…The worker/patient, the employer, the healthcare provider, and the insurer, are all involved in the work disability process, often in complex interplays [7][8][9][10]. Also, the process of return to work (RTW) following ill health has a multifactorial nature, including complex interactions between (1) biological, psychological, and social factors as well as (2) different ''systems'', such as the personal, workplace, health care and insurance system [7,9,[11][12][13]. Moreover, work disability and RTW processes and practices have to be understood and appreciated within the specific administrative and jurisdictional context [7,11,14].…”
Section: Introductionmentioning
confidence: 99%